Kajian Pengembangan Kampung Nelayan Malabero yang Terintegrasi Dengan Kawasan Wisata Kebun Keling - Deslei Aulianti; Mussadun Mussadun (Teknik PWK (Perencanaan Wilayah Kota), 2016)
Malebero regency is located in the coastal city of Bengkulu with a majority population of livelihood as a fisherman. Kampung Nelayan Malabero has great tourism potential, both in terms of ecology and society’s culture. Malabero fishing village is located in the famous tourist area and the historical area in Bengkulu. Some tourist sites in this area are Tapak Paderi and Fort Malborough. Although the location close to the tourist areas, Malabero fishing villages looks like slum area and gives contrast impression to tourist sites that close to the village. The purpose of this study was to determine the efforts for the development of Kampung Nelayan Malabero that integrated with Kebun Keling tourist area. The method used in this research is qualitative method with descriptive analysis. The data used in this study were collected through interviews with Malabero fishing village’s community, tourists and other related agencies, literature studies and observation. The samples that taken in this study using snowball sampling technique. Based on the survey and analysis results that Malabero fishing village has the potential of tourism development which can be integrated with Kebun Keling tourist areas such as the development efforts for both regions.